Some new observations on fixed point results in rectangular metric spaces with applications to chemical sciences - Younis, Mudasir; Fabiano, Nicola; Fadail, Zaid M.; Mitrović, Zoran D.; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: This paper considers, generalizes and improves recent results on fixed points in rectangular metric spaces. The aim of this paper is to provide much simpler and shorter proofs of some new results in rectangular metric spaces.Methods: Some standard methods from the fixed point theory in generalized metric spaces are used.Results: The obtained results improve the well-known results in the literature. The new approach has proved that the Picard sequence is Cauchy in rectangular metric spaces. The obtained results are used to prove the existence of solutions to some nonlinear problems related to chemical sciences. Finally, an open question is given for generalized contractile mappings in rectangular metric spaces.Conclusions: New results are given for fixed points in rectangular metric spaces with application to some problems in chemical sciences.
Keywords: fixed point; rectangular metric space; contractive map; Green function